A comparative study on the interface tension and interface dilational rheological properties of three sodium N-acyl aromatic amino acid surfactants. Issue 44 (10th July 2020) - Zhang, Fan; Zhang, Qun; Yang, Jian; Zhou, Yawen; Zhou, Zhaohui; Wang, Ce
Abstract : Interface dilational rheology is useful for understanding and exploring the role of interface phenomena. Abstract : Interface dilational rheology is useful for understanding and exploring the role of interface phenomena. However, relatively few studies have been conducted on the interface dilational rheological properties of N -acyl aromatic amino acid surfactants. Herein, surface tension and the dynamic interface tension and dilational rheological properties of three surfactants, namely, sodium N -lauroyl phenylalaninate (SLP), sodium N -lauroyl tyrosinate (SLTy), and sodium N -lauroyl citrate (SLTr) were investigated. The results show that the order of critical micelle concentration, which includes the surface tension at the critical micelle concentration, minimum area per surfactant molecule, and interfacial tension, was SLTr < SLTy < SLP. At a low surfactant concentration, the three surfactants exhibited a low-viscosity interfacial elastic film at the n -decane/water interface. The dilational modulus increased and the phase angle decreased with increase in frequency. However, the order of the dilational modulus was SLP < SLTy < SLTr, while the order of the phase angle change was SLTr < SLTy < SLP at the same frequency. With increase in surfactant concentration, the dilational modulus of SLP and SLTy increased and then decreased after a maximum value; however, the dilational modulus plot of SLTr demonstrated two maxima.